Acquired Pediatric Right Diaphragmatic Hernia Following Automatic Implantable Cardioverter-defibrillator Placement - Ottoboni, Adria (Clin Pract Cases Emerg Med, 2019)
Diaphragmatic hernias are an uncommon occurrence in the pediatric population; however, they can cause significant morbidity and mortality if the diagnosis is missed or delayed. This case discusses the radiographic and clinical exam findings of a one-year-old patient with this pathology.